Effects of classroom response system on the achievement and knowledge retention of the students in mathematics - Jayson Virtucio Alviar; Anabel Enriquez Gamorez (Cogent Education, 2024)
AbstractClassroom Response System (CRS) is a promising educational tool that can create an interactive learning space. In high school, less is known about its impact on learning mathematics. Most studies on the integration of CRS in teaching and learning use internet-dependent tool. This paper aimed to determine the effectiveness of the CRS that uses Bluetooth technology in improving the mathematics achievement and knowledge retention of the students. A quasi-experimental design and longitudinal study with post-test and delayed post-test was employed in this study. The assessment and re-administered assessment results of the CRS and Traditional Classroom Instruction (TCI) groups were compared. Data were analyzed using an independent sample t-test and Welch t-test, and the Mean Percentage Scores (MPS) were calculated to determine the achievement level. Findings revealed that there was a significant difference between the assessment of the CRS and the TCI groups. Moreover, the re-administered assessment results suggest that students exposed to CRS have better knowledge retention compared to the TCI. Furthermore, the MPS showed that CRS exhibited higher mastery level of the learning competencies over the TCI group. This study provides valuable insights into the integration of CRS in mathematics teaching and its consequential effect on achievement and retention.